YOUNG NEW ZEALANDERS AND FINANCIAL RESILIENCE IN THE TIME OF COVID-19: A LONGITUDINAL STUDY UPDATE - Matthews C; Reyers M; Wood P; Stangl J (Fin-Ed Centre, 2021)
This report covers an interim update to the 20-year longitudinal study into how young New Zealanders learn about personal finance. The main longitudinal study, conducted at five-early intervals, launched in 2012 and comprised a cohort of New Zealanders aged 18 to 22 years, at that time. The second stage of the study took place in 2017 and the third stage will take place in 2022. Overall, the Longitudinal Study endeavours to understand issues related to the financial knowledge and financial education experience, both formal and informal, of the participants. Planned interim updates, such as this, enable on-going contact with the participants as well as providing a periodic snapshot of their financial knowledge progression and financial wellbeing. The study previously undertook interim updates in 2014, 2016 and 2019.
Keywords: Financial literacy; Longitudinal study; Covid-19